IMPLEMENTATSIJA UKRAINE OF SYSTEM OF TECHNICAL REGULATION OF EU: ECONOMY AND LEGISLATIVE ASPECT - S. Ivanov; M. Artyuh (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In work it is investigated economy and is standard-legal consequences which come after signing of Ukraine of the Agreement about a zone of free trade from EU. Essential calls concerning signing of the Agreement are defined by Ukraine which causes implementatsija systems of technical regulation of EU. It is investigated most prominent aspects of technical regulation of Ukraine in a direction of the horizontal and branch legislation which need immediate reforming.